2016
DOI: 10.4103/2249-4863.197279
|View full text |Cite
|
Sign up to set email alerts
|

Profile of trauma patients in the emergency department of a tertiary care hospital in South India

Abstract: Background:Trauma is an increasing cause of morbidity and mortality in India. This study was done to improve the understanding of the mode of trauma, severity of injuries, and outcome of trauma victims in our hospital.Materials and Methods:This was a retrospective observational study of all adult trauma patients more than 18-year-old presenting to our emergency department (ED). Details of the incident, injuries, and outcome were noted.Results:The ED attended to 16,169 patients during the 3-month study period w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 8 publications
3
23
0
2
Order By: Relevance
“…Similarly, the mean age of the multiple trauma patients in the study is 41.34 ± 19.41 years. This is consistent with the earlier reports which were conducted in other regions such as India 17 and Iran, which are also recognized as developing regions. 14 Concerning the clinical characteristics of the patients, RTA is observed to be the most primary source of trauma among the patients.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, the mean age of the multiple trauma patients in the study is 41.34 ± 19.41 years. This is consistent with the earlier reports which were conducted in other regions such as India 17 and Iran, which are also recognized as developing regions. 14 Concerning the clinical characteristics of the patients, RTA is observed to be the most primary source of trauma among the patients.…”
Section: Discussionsupporting
confidence: 93%
“… 4 – 6 Among patients with trauma, FFH is the second most common cause of injury-associated mortality after road traffic accidents in India. 7 Literature review from the West suggests that the injuries caused by falls are more likely to be life-threatening than most other types of injuries. 8 , 9 These incidents mainly include occupational accidents in the construction industry and may lead to permanent disabilities and a high rate of fatalities.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study RTAs were the predominant cause of trauma, a result consistent with other studies from India and abroad. 7,15 Four wheel vehicles offer a fair amount of protection to those inside unlike two wheeler passengers and pedestrians who are directly exposed to the elements of the road. This explains the overwhelming majority of the accidents involving two wheelers and pedestrians, consistent with other Indian studies.…”
Section: Resultsmentioning
confidence: 99%
“…A study done in North Ireland found the mean duration of presentation after hand injury to be 2.9 hours while a study from hospital in southern India found the mean duration to arrival at hospital to be 3 hours. 7 In low income countries like India, pedestrians, cyclists, motorized two wheeler vehicle users are exposed to a higher risk for hand injuries than 4 wheeler users. 4 Risk factors contributing to the higher rate of incidence were found to be excessive speed, use of alcohol and drugs, young male, poor visibility on roads, non-use of seat belts and helmets etc.…”
Section: Introductionmentioning
confidence: 99%